Reestructuración técnico administrativa en la empresa Friparts S.A.S. (2019)
The present degree work was carried out in the company Friparts SAS, located in the city of Bogotá DC, where an administrative technical restructuring is carried out, through which it seeks to propose solutions to various problems that arise both internally as an external company through the use of industrial engineering tools.